MEASUREMENT CT SCAN OF THE JAW BONE AS A PANORAMIC RADIOGRAPHY FACTOR CORRECTION TOWARDS PANORAMIC USED FOR DENTALIMPLANT PLACEMENT: PENGUKURAN CT SCAN PADA TULANG RAHANG SEBAGAI FAKTOR KOREKSI TERHADAP PANORAMIK UNTUK PE NEMPAT AN IMPLAN GIGI - Barunawaty Yunus (Dentika: Dental Journal, 2010)
One of the important factors that plays a role in the succ ess of dental implant treatment is the accuracy of evaluating thequality and quantity of jaw bone. Parameter of quality and quantity of jaw bone that will receive the implant is the bonepicture of diagnostic information in three dimensional objects which are the thickness, width and height of the jaw bone.To obtain information, digital technolog y such as CT Scan is needed in order to get the parameters of the jaw bone whichis relatively more accurate. This study aimed to assess the measurement of CT Sca n in the jaw bone as a correction factorof the panoramic radiography for dental implant placement. Th e study was a cross sectional. Analysis t he subjects usedjaw bones patient who had lost a posterior maxilla or mandible . T otal sample was 60 jaws, each s ample went through CTscan and Panoramic radiography to know the thickness, width and length of the jaw bone used for dental implantplacement. The results showed that there was significant difference p<0.05 )), of the length of the jawbone between on CTSc an and Panoramic radiography. I t can be concluded that CT Scan is a tool that can assess jaw bone measurement that ismore accurate than Panoramic radiography for dental implant placement.